Konsekwencje zmian polityczno-ekonomicznych w Rosji po upadku komunizmu - Stankiewicz, Wojciech (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
On the basis of analysis of the transformations occurring in Russia following the collapse of Communism, the Author proposes a research hypothesis in terms of three statements. Firstly, Russia is creating the foundations for the development of a market economy, yet this process is hardly dynamic and has not involved all the branches of the economy. Secondly, there are no symptoms to demonstrate that a civic society is emerging in Russia, with tradition playing a significant role in how the relations between the elements and social institutions are perceived. Thirdly, the Kremlin’s foreign policy is not clearly formulated, and no transparent strategy or clear objectives have been worked out.